Alternative Approach for Pulmonary Valvuloplasty in Critical Congenital Pulmonary Stenosis - Ara, Andaleeb; Akhtar, Khurram; Rafique, Saima (Pakistan Armed Forces Medical Journal, 2022)
Critical congenital pulmonary stenosis with intact interventricular septum is a cyanotic and potentially lethal neonatal cardiac anomaly. Percutaneous transcatheter balloon pulmonary valvuloplasty for critical pulmonary stenosis often presents technical difficulties due to supra-systemic pressure in right ventricle. Using transjugular approach instead of the femoral vein helps in dealing with this issue. We describe the successful use of right internal jugular vein approach in a case of critical pulmonary stenosis.